2021
DOI: 10.1007/jhep03(2021)196
|View full text |Cite
|
Sign up to set email alerts
|

Discrete and higher-form symmetries in SCFTs from wrapped M5-branes

Abstract: We analyze topological mass terms of BF type arising in supersymmetric M-theory compactifications to AdS5. These describe spontaneously broken higher-form gauge symmetries in the bulk. Different choices of boundary conditions for the BF terms yield dual field theories with distinct global discrete symmetries. We discuss in detail these symmetries and their ’t Hooft anomalies for 4d $$ \mathcal{N} $$ N = 1 SCFTs arising from M5-branes wrapped on a Riemann surface without punct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 50 publications
(144 reference statements)
0
53
0
Order By: Relevance
“…A BF coupling is related to a Stückelberg mechanism by dualization of a p-form gauge field (as reviewed for instance in [44]). Thus, the main physical mechanism observed in the present setup is the same as in [43]. Their 11d origin, however, is different: while in [43] all BF couplings originate from the C 3 G 4 G 4 Chern-Simons term in the M-theory effective action, in the solutions of this paper the Stückleberg coupling originates from a non-trivial Bianchi identity, which is required by self-consistency of G 4 after the Kaluza-Klein vector A β is turned on.…”
Section: Jhep11(2021)140mentioning
confidence: 79%
See 1 more Smart Citation
“…A BF coupling is related to a Stückelberg mechanism by dualization of a p-form gauge field (as reviewed for instance in [44]). Thus, the main physical mechanism observed in the present setup is the same as in [43]. Their 11d origin, however, is different: while in [43] all BF couplings originate from the C 3 G 4 G 4 Chern-Simons term in the M-theory effective action, in the solutions of this paper the Stückleberg coupling originates from a non-trivial Bianchi identity, which is required by self-consistency of G 4 after the Kaluza-Klein vector A β is turned on.…”
Section: Jhep11(2021)140mentioning
confidence: 79%
“…We conclude this section with a comparison with the spontaneously broken U(1) symmetries in M-theory discussed in [43]. In that reference, the focus is on U(1) p-form symmetries originating from the expansion of the M-theory 3-form C 3 onto cohomology classes.…”
Section: Jhep11(2021)140mentioning
confidence: 97%
“…The defect group measures the defects which are not screened by dynamical objects, and as we will see, it is defined by the (relative) homology of W 6 . It has been shown that this object is readily computable through several methods [20][21][22][23][24][25][26][27][28][29][30][31] giving us considerable insight into the higher form symmetries of various field theories.…”
Section: Jhep10(2021)119mentioning
confidence: 99%
“…choosing a global form of the gauge group and possible discrete theta parameters [12] (see also [1]). More recently work related to the higher form symmetry of 4d SCFTs and holography was studied in [13]. In the context of non-Lagrangian 4d N = 2 SCFTs of Argyres-Douglas type the 1-form symmetries were computed using the Type IIB realization using canonical singularities in [14,15], using the general observations in [16][17][18], which are applicable more generally to geometric engineering of SCFTs in string theory.…”
Section: Introductionmentioning
confidence: 99%